ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN EKONOMI DI KOTA BANDUNG - Saputra Wiguna, Ade; Debby Arisandi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
This research aims to analyze the factors influencing economic growth in the city of Bandung. Through interviews with stakeholders and analysis of recent economic data, factors such as the small- scale industry sector, infrastructure, waste management, tourism, per capita income, and the field of accommodation and food services are evaluated to understand their impact on the city's economic growth. The results indicate that the small-scale industry sector plays a significant role, along with infrastructure and waste management, in driving positive economic growth. Additionally, tourism, per capita income, and the field of accommodation and food services also make important contributions. This research provides an in-depth understanding of key factors that need attention for designing policies that support sustainable economic growth in Bandung.